Virtual Screening of Mimosa pudica Secondary Metabolites as Hyaluronidase B Potential Inhibitor to Prevent Vespa velutina Venom Spreading - Rijalullah, Muhammad Asyraf; Pramudya, Muhammad Alif Imam; Maisuroh, Dalilatul; Zain, Dhiyaa Syahlaa Bianca Febrinnisa; Kurniawan, Nia; Fatchiyah, Fatchiyah (JSMARTech, 2021)
Vespa velutina, also known as the Yellow-legged hornet, is a wasp species native to Asia with a large distribution area in Indonesia. Hyaluronidase B in a wasp venom acts as a